Fully-automated production of [68Ga]Ga-PentixaFor on the module Modular Lab-PharmTracer - Sarah Spreckelmeyer; Oliver Schulze; Winfried Brenner (SpringerOpen, 2020)
Abstract Background PentixaFor is a promising radiopharmaceutical for positron emission tomography in the detection of different tumor entities and other diseases. Until now, the synthesis of [68Ga]Ga-PentixaFor was reported for the automated synthesis module from Scintomics® only. Our aim was to evaluate the automated synthesis of this radiopharmaceutical on a different module in order to make it available for a broader community. Results The synthesis of [68Ga]Ga-PentixaFor with different amounts of PentixaFor (50 μg, 30 μg and 20 μg) on the Modular Lab PharmTracer (MLPT) from Eckert & Ziegler with the already established synthesis template for [68Ga]Ga-DOTATOC yielded best results with 50 μg PentixaFor for clinical multi-dose application. All different quality control parameters tested (e.g. sterility, stability and radiochemical purity) were in accordance with the European Pharmacopoeia. Conclusions [68Ga]Ga-PentixaFor was successfully synthesized fully-automated on the synthesis module Modular Lab PharmTracer and can be used for multi-dose application in clinical settings.